The current state of the training process for amateur athletes in triathlon - Ovcharenko , M.; Dolbysheva , N. (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. The popularity of triathlon on the world sports arena is constantly growing, and in particular, non-Olympic triathlon programs are rapidly gaining competitiveness among different age groups of amateur athletes, which prompts the search for new ways of organizing the educational and training process. To date, the problems of individualization of the training process and the integration of innovative technologies into the educational and training process of amateur athletes in triathlon for effective planning of independent classes in the system of private sports clubs have not been fully covered. That is why the development and implementation of the program for the physical training of amateur athletes in the non-Olympic triathlon program becomes relevant in the context of the development of the triathlon industry. The aim of the study: To determine the peculiarities of the organization of the training process and the importance of physical training of amateur athletes in triathlon in the system of private sports clubs. Material and methods: method of analysis of scientific and methodological literature, method of analysis of the regulatory framework, sociological survey of triathlon coaching staff, method of expert evaluation. 9 experts who are triathlon coaches and have a higher education (11-15 years of coaching experience) took part in the survey, among them: 1 – Honored Coach of Ukraine, 1 – second category, 7 – no category. Of the mentioned experts, 7 work in the system of private sports clubs. The sociological survey was conducted using a questionnaire comprising questions related to the methods of organizing the educational and training process and the structure of physical training of amateur athletes in the non-Olympic triathlon program. The questions had both open-ended and closedended formats. The results. As a result of the conducted research, it has been established that the organization of the educational and training process for amateur athletes in non-Olympic triathlon requires an integrated approach that takes into account the age groups of athletes, their individual characteristics, and training conditions. The optimal allocation of time between independent sessions and training within the private sports club system contributes to a more effective preparation of amateur athletes, as indicated by 88.9% of respondents. The use of innovative remote technologies helps optimize the educational and training process, facilitates communication between coaches and athletes, and enhances the effectiveness of progress analysis and training program adjustments. These findings are supported by expert assessment. Conclusions. The organization of the educational and training process of amateur athletes in the non-Olympic triathlon requires an integrated approach and a personalized organization of training, which are based on the distribution of time for training classes (in the club system and independent classes), individualization of approaches to means and methods of physical training, and the use of modern innovative remote technologies.